Rational drug use in elderly patients in a primary care center - Bahadir Yazicioglu; Elif Dikmetas Yardan (Journal of the Pakistan Medical Association, 2021)
Objective: The objective of the research was to examine and evaluate rational drug uses of patients over 65 years of age referring to Primary Care Center. Methods: A questionnaire on the drug usage habits of elder patients prepared by making literature scanning and taking expert view was applied in the study to the participants accepting to join the study among patients over 65 years of age applying to Family Health Center. Results: A total of 291 patients including 127 males (43.6%) and 164 females (56.4%) over 65 years of age were included in the study. Mean age of the participants was found 72.76. Leftover drug keeping ratio of the participants at home was found as 53.3% (n=155). When unprescribed drug usage conditions of the participants were questioned, 60.8% (n=177) stated that they didn’t use unprescribed drugs. Conclusions: Polypharmacy is an important health problem for elder individuals with the lengthening of average duration of life and increase in the prevalence of chronic diseases. Drug use for a wrong time and dose may cause conditions such as the lack of the effect which should be provided by the drugs, or occur more than expected or unexpected drug-nutrient interactions. Primary care physicians have an important role in disease and health phases of elder patients. Keywords: Aging, Drug therapy, Drug misuse, Continuous...